Investigation of Adoption and Cognizance of Urban Green Spaces in India: Post COVID-19 Scenarios - Bherwani, Hemant; Indorkar, Tushar; Sangamnere, Ravindra; Gupta, Ankit; Anshul, Avneesh; Nair, Moorthy M.; Singh, Anju; Kumar, Rakesh (Current research in environmental sustainability, 2021)
Urban open and green spaces provide various ecosystem services such as aesthetics, biodiversity, recreation and most importantly health. These spaces, especially in an urban area, are beneficial for the physical and mental health of people. These services become more important at the time of social and health crisis such as COVID-19. Access to urban open and green space with suitable precautionary measures such as social distancing and personal hygiene would have improved individuals resilience during the pandemic. Due to the COVID-19 imposed lockdown, people were forced to isolate with no access to any of the recreational spaces to combat the global challenge. Once the lockdown was eased in India, the public focus shifted towards the need for urban green and open spaces along with hygiene. The present study examined the change in need, usage patterns, hygiene and infrastructure facilities for such urban green and open spaces in cities. Multi-parameter analysis was conducted for the data collected from 27 cities, especially with respect to age and behavioral patterns. 170 valid responses for the designed survey were received from 27 Indian cities and towns. The results indicated that these areas were important for a wide range of activities, such as walking and jogging, relaxation, health, and yoga, meeting with friends, etc. The study results show that 62.35% of people feel that urban open and green spaces should be increased while 31.18% of people feel that more facilities should increase in current open and green spaces. 85% of people feel that yoga activities have increased in urban open and green spaces during post COVID-19 imposed lockdown compared to pre COVID-19 era. 99% of individuals agree that to make their immune system healthy and to mentally and physically prepare for such pandemic, they need to more often use green spaces for yoga and other health-related activities. Whereas, 90% of visitors admitted that urban green and open spaces help them cope with their physical and mental health concerns. People started using green and open spaces for productive purposes and avoided social gatherings as far as possible in such areas. The results were validated with statistical analysis using ANOVA in MINITAB14. The statistical analysis indicates a clear effect of age group and lockdowns on the people's activities, specially for Health and Yoga with p < 0.05 at confidence interval of 95%. The study conclusively demonstrates that open and green spaces are certainly needed in urban areas to maintain the mental and physical health of people and COVID-19 has redfined the importance of urban open and green spaces to the residentis of urban areas. Overall, COVID-19 pandemic must be considered as as impetus situation in planning a sustainable and health resilient city. [Display omitted]